Influência da densidade populacional na fenologia e na produtividade da cultura do milho - Oliveira, Juan Paulo Padilha de (2014)
The field survey was conducted in Palmeira das Missões, with the objective of evaluating the effect of plant population on yield of maize (Zea mays) under different populations (70,000, 85,000, 95,000, 100,000, 105,000, 111,000, 120,000 and 151,000 plants/ha), in two handling areas, a plane sloping terrain and the other relief, on each of these consisted 8 replicates. Between different reliefs , the increase in population density of maize showed significant difference in stem diameter , however , within the same zone management was no significant difference in specific objectives , with the exception of stem diameter .Thus grain yield was directly influenced by plant population and its variation can be an excellent option, especially for producers with different topographies within the same area. This indicates that within the same area, it is possible to increase the yield with the variation in plant population.